Development of a computational tool to analyze sounds: A biological study with anuran - Salgado Costa, Carolina (2016)
The emission of underwater sounds in anuran tadpoles has been documented in only two species from Argentina and one from Madagascar. Underwater sound emission by Ceratophrys ornata (Anura: Ceratophryidae) tadpoles was a novel finding reporting the first evidence in anuran larvae. The sound has been described as part of an antipredator mechanism that diminishes the frequency of predation between conspecifics. The aim of the study was to describe sound variability from tadpoles to adults with a novel technique in bioacoustics. Sounds emitted by tadpoles were both recorded underwater and out of water. The recording system consisted of a microphone and an interface coupled with a laptop. It was first calibrated with an acoustic reference source and compensated in order to obtain a recording system with flat frequency response. Audio recordings were digitalized, and post processed by a computational tool specifically developed in a numerical environment software. Variables selected to describe basic structure of sounds were: sound duration, number of pulses, number of inter pulses and dominant frequency. These variables were supplemented with typical acoustic parameters, such as equivalent continuous pressure level, peak sound pressure level, and spectral analysis with constant bandwidth filters. The interdisciplinary experience allowed developing a reliable system of recording, analysing thousand of sounds in a short period and therefore characterizing the sound of a species considering all variability.